THE IMPRESSION OF HALAL LABEL AND CELEBRITY ENDORSMENT ON PURCHASING DESICION FOR MSGLOW COSMETIC PRODUCTS: MS GLOW CONSUMER STUDY IN LHOKSEUMAWE CITY - Nurfajri; Ichsan; Mukhlish M. Nur; T. Saifullah (IAIN Lhokseumawe, 2023)
This study aims to This study aims to determine the effect of halal labels and celebrity endorsements on purchasing decisions for MS Glow Cosmetic Products (MS Glow Consumer Study in Lhokseumawe City). The data used in this study are primary data of 91 respondents. The method used to analyze the relationship between the independent variables and the dependent variable is multiple linear regression analysis. The results showed that partially the halal label had a positive and significant effect on purchasing decisions for MS Glow Brand Cosmetic Products in Lhokseumawe City and signifikan level 0,000, Celebrity endorsements had a positive and significant effect on purchasing decisions for MS Glow Brand Cosmetic Products in Lhokseumawe City and signifikan level 0,041. Simultaneously Halal Label and Celebrity endorsement have a positive and significant effect on purchasing decisions for MS Glow Brand Cosmetic Products in Lhokseumawe City and signifikan level 0,000.